CONVERGENCE IN THE DEVELOPMENT OF SOUTH SLAVONIC AND GREEK PRONOMINAL SYSTEMS - Bubenik, Vit; Milovanovic, Snezana (Linguistica Atlantica, 1993)
Section 1 introduces one of the salient Balkanisms - the ’proleptic use of pronouns’, called crossindexing of the direct and indirect objects / clitic doubling constructions - in the context of other Balkanisms. The necessary diachronic background for the present study, case syncretism and the emergence of the postpositive article in South Slavonic languages, is provided in 2 and 3. The development of the Bulgaro-Macedonian pronominal system from that of Old Church Slavonic is outlined in 4, and the parallel development of the Greek system in 5. The current controversy regarding the synchronic status of Modern Greek and Bulgaro-Macedonian clitics is addressed in 6. It is demonstrated that pronominal clitics of Modern Greek cannot be considered to be bound morphemes and that Macedonian clitics stand a better chance to qualify for the status of bound morphemes / affixes vis-a-vis those of Greek but also those of closely related Bulgarian. Section 8 attempts to establish a causal nexus between the loss of case and the emergence of crossindexing of the recipient / beneficiary and the patient by means of clitic doubling constructions. Modern Greek went as far as Middle Bulgaro-Macedonian before the loss of case marking on the definite article; Macedon ian, however, converged with Greek in favouring the strategy of proclisis vs. Bulgarian enclisis: ton=vlepo, ton=j6 (Greek) and go=gledam sinot vs. gledam=go, sina (Bulgarian) ’[ see the son’. Furthermore, only Macedonian demarked this construction in that the doubling is necessary outside pragmatic contexts. Morphological corollaries are the uninterruptibility of the clitic block recipient=patient and its immediate attachment to the verb in Macedonian (vs. Bulgarian). Some desiderata for further typological and functional research along the lines of the present study are outlined in 7 and 9.